الجهود الجزائرية والتونسية في ظل التضامن مع الدولة العثمانية ودول المحور خلال الحرب العالمية الأولى (1914-1918) (El-Wahat Journal for Research and Studies, 2023)
ملخص:شكل التضامن عنصر أساسيا في تاريخ العلاقات العربية العثمانية، ومن أمثلة ذلك التضامن الكبير الذي جمع بين سكان الجزائر وتونس والدولة العثمانية خلال الحرب العالمية الأولى، حيث رأوا ان الدولة العثمانية تمثل عاصمة للخلافة الإسلامية وكان في نظرهم أن التحالف ضروري من أجل نصرة بلاد الإسلام.وفي هذا المقال سنتطرق الى مظاهر التضامن التونسي والجزائري مع الدولة العثمانية ودول المحور في الحرب العالمية الأولى، وذلك من خلال التعرف على دعائم العلاقة بين الدولة العثمانية وسكان تونس والجزائر قبيل الحرب العالمية الأولى، والوقوف على الدعاية العثمانية وكذا مساهمات الجزائر وتونس في دعمها والتجند في صفوفها.كلمات دالة: الجهود الجزائرية,التضامن التونسي, الدولة العثمانية, دول المحور, الحرب العالمية الأولى.   Abstract:TheSolidarity was an essential element in the history of the Ottoman Arab relations, and example is the great solidarity that brought together the inhabitants of Algeria and Tunisia and the Ottoman Empire during the First World War, where they saw that the Ottoman Empire represents the capital of the Islamic caliphate and in their view that the coalition is necessary for the victory of the land of Islam.In this article, we will look at the aspects of Tunisian and Algerian solidarity with the Ottoman Empire and the Axis of the First War, by identifying the foundations of the relationship between the Ottoman Empire and the inhabitants of Tunisia and Algeria before the First World War, and to determine the Ottoman propaganda, as well as the contributions of Algeria and Tunisia in its support and recruitment in its ranks . Key words:The Algerian efforts, Tunisian solidarity, Ottoman Empire, Axis countries, World War I